Influence of Different Disinfectants on Surface Hardness of Heat-Polymerized Acrylic Resins utilized for Orthodontic Appliance - Wael Abdul Alrazzaq Alwaeli; Mohammed Abdul Sattar Alsegar (Journal of Techniques)
Heat-polymerized resins are common substances utilized for construction of removable dental prostheses (i.e. Orthodontic appliances). Such materials should have appropriate physical properties. The use of disinfectant solutions might influence the physical characteristics of the acrylic materials.  This study was conducted to assess the influence of different disinfectants on heat polymerized resins in terms of surface hardness. Forty specimens were made from heat-polymerized acrylic resins in total. The investigation comprised 4 groups according to the disinfectants utilized and each group had ten specimens. The 1st group was immersed in distilled water (control); the 2nd group was disinfected in Efferdent; the 3rd group was disinfected in 4 % Chlorhexidine; and the 4th group was disinfected in 1% hypochlorite. All specimens were tested via a hardness tester three times and the average reading was measured for all specimens. The statistical results indicated a slight decline in the mean values of surface hardness of acrylic specimens following immersion in disinfectants. The greatest value of mean was for distilled water specimens whereas the lowest value of mean was for 4% Chlorhexidine specimens. Furthermore, no significant differences were found among all groups (P>0.05). The study concluded that the use of disinfectants solutions slightly decreases the hardness of heat polymerized resins. It is recommended to evaluate the chemical interaction between the acrylic resins and disinfectants.